INFILTRATION RATE AND CAPACITY IN PINE AGROFORESTRY IN CIDURIAN SUB WATERSED, BANDUNG, JAWA BARAT - Karimatunnisa, Sakinah
Land cover changes in the upstream area of the Cidurian sub-watershed there is located in Cimenyan Village resulted the changes in soil physical properties that will affect the ability of the soil to absorb water. The process of water entry into the ground (infiltration) is the initial process of entry of water into which will later become a discharge input for springs. This study aims to determine the infiltration capacity in the catchment area. Measurements were taken from February - June 2019. The infiltration data was collected using a single-ring infiltrometer, by the stratified random sampling method and at each statification 5 points were taken. The results showed that the Pine-Coffee agroforestry area had a lower infiltration rate than the Pine-Chili-Coffee agroforestry area of 26.76 ± 2.41 cm / hour and 86.75 ± 5.06 cm / hour both of which entered very fast category in the classification of infiltration rates according to Uhland (1951). However, the infiltration capacity in the Pine-Coffee agroforestry area is greater than the Pine-Chili and Coffee agroforestry areas, which is 2236.98 ± 2.41 m3 / hour and 2107.49 ± 5.06 m3 / hour. After conducting statistical tests, one of the factors that influence it is the amount of litter and water content in the greater Pine-Coffee agroforestry area, the potential of litter water content makes the infiltration rate occur slowly but in a longer period of time, that factor make the process of water entry into in the soil can occur in a longer time.